Empowering Local Communities: A Public Governance Advocacy Framework for Sustainable Tourism Development - Amni Zarkasyi Rahman; Dyah Lituhayu; Prihantoro; Nilam Adini Rakhma (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
This research investigates an advocacy framework for sustainable tourism development, focusing on a public governance approach that prioritizes community empowerment and collaborative practices in Glawan Village, Semarang Regency, Indonesia. Glawan, a unique case study due to its blend of cultural heritage and strong community involvement, serves as an emerging model for rural tourism. The study utilizes a qualitative methodology, including in-depth interviews and focus group discussions with key stakeholders such as local government officials, community leaders, and tourism practitioners. Findings reveal that the advocacy framework, which integrates local wisdom, ecotourism, and participatory governance, is instrumental in shaping the village's tourism growth. Critical factors like attractions, accessibility, public facilities, and community engagement are identified as pivotal drivers. The research underscores the multifaceted role of the local government, which acts as a facilitator in planning, managing, and coordinating tourism while ensuring stakeholder collaboration. Ultimately, Glawan Village demonstrates that an advocacy-based approach, emphasizing community-led initiatives and multi-stakeholder synergy, can successfully balance economic viability, cultural preservation, and environmental responsibility. This study offers a replicable blueprint for policymakers and community leaders aiming to foster sustainable, resilient, and community-driven tourism.